Conclusion: An invitation to dialogue with The Life of the Mind. (June 2022) - Marková, Ivana; Brinkmann, Svend; Cabra, Martina; Coultas, Claire; Zadeh, Sophie; Zittoun, Tania
In this conclusion to the special issue on The Life of the Mind by Hannah Arendt, we, the authors, reflect back on our dialogue with the philosopher's text. Our reflexion has two main parts. First, we emphasise transversal themes – themes that most triggered our interrogations and that we as psychologists, all addressed in our separate papers: thinking, of course, but also Arendt's views on dialogue, her conception of time and temporality, and morality. Second, we emphasise some of the questions emerging from our reading of Arendt, which, we feel, can enrich discussions in psychology, and especially in cultural psychology today. Altogether, we conclude by inviting readers to join in our dialogue.